Recycling and reuse of glass cullet proceedings of the international symposium organised by the Concrete Technology Unit and held at the University of Dundee, Scotland, UK on 19 - 20 March 2001 - Dhir, Ravindra K.; Limbachiya, Mukesh C.; Dyer, Thomas D. (Thomas Telford, 2001)
The necessity for adopting sustainable practices is becoming increasingly clear, and the recovery of maximum value from surplus glass cullet is a key component in this. The concrete construction industry can provide a number of alternative uses for cullet that can add value to this waste material. The topic is covered by these conference proceedings.